PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DAN DANA ALOKASI KHUSUS (DAK) PADA PERTUMBUHAN EKONOMI DAERAH PROVINSI SULAWESI UTARA - Virginia ., Laloan; O. Esry H. Laoh; Caroline B. D. Pakasi (Sam Ratulangi University, 2018)
This study aims to examine the effect of original income, general allocation funds and special allocation funds to regional economic growth in North Sulawesi Province. This research was conducted for three months starting from October until December 2017 in North Sulawesi Province. In this study the data used are secondary data obtained from the Central Bureau of Statistics (BPS) of North Sulawesi Province. The data is processed using descriptive analysis research method and presented in tabular form. The resulting data were analyzed by using multiple linear regression. The result of the research shows that the local revenue (PAD) significantly influences economic growth, but negatively impacts the economic growth in north Sulawesi, the general allocation fund (DAU) has a significant effect and has a positive effect on economic growth in North Sulawesi Province and The Special Allocation Fund (DAK), shows that there is no significant effect on economic growth in the Province of North Sulawesi.